ANALISIS SEMIOTIKA PESAN DAKWAH DALAM PUISI “SAJADAH PANJANG” KARYA TAUFIQ ISMAIL - Fatma Laili Sa’adah, Zukha; Fakhruddin Fajrul Islam, Ahmad (Spektra Komunika : Jurnal Komunikasi & Dakwah, 2024)
The literary works of Taufiq Ismail, an Indonesian cleric and writer, embed Islamic values within his creations, including the poem "Sajadah Panjang." This poem, characterized by its beautiful yet accessible language, possesses a magical allure that captivates readers and listeners alike, inviting them to experience reverence in connecting life with the divine. Adapted into lyrics and sung by Bimbo and Noah, the poem further enhances its solemnity and popularity among the public. This research aims to uncover the message of Islamic propagation contained within Taufiq Ismail's poem "Sajadah Panjang." Employing a qualitative descriptive approach and the semiotic analysis method of Michael Rifatterre's model, the researcher examines discontinuities in expression, heuristic and hermeneutic readings, matrix searches, models, variants, and determines the hypogram text as the genesis of the poem's creation. The research findings reveal the propagation message encompassing two main issues: the outward and inward aspects of worship, and belief in Allah SWT. This poem serves as a reminder of life's meaning, bridging existence with the greatness of the Divine and our obligations to Him